Konstruksi Skizofrenia dalam Video Klip Halu-Feby Putri - Muhammad Zahran Arrafi; Altobeli Lobodally (UNIVERSITAS KALBIS, 2022)
Schizophrenia is a mental disorder that sufferers experience over a long period of time. Schizophrenia is the theme of the concept and theme in Feby Putri's video clip titled